Marketing fashion footwear the business of shoes - Armstrong-Gibbs, Fiona; McLaren, Tamsin (London Bloomsbury, 2017)
"Marketing Fashion Footwear addresses the strategic issues surrounding the marketing and distribution of footwear, including brand identity, consumer behavior, production and manufacturing, and the impact of globalization and regional trends"--Provided by publisher.
1. The Fashion Footwear Consumer -- 2. Footwear Design, Construction, and Production -- 3. The Global Footwear Trade -- 4. The Retail and e-Tail Landscape -- 5. Management Strategies for Retail Growth -- 6. Visual Merchandising and Design Concepts for Retail, E-tail, and Wholesale -- 7. Brand Identity and Protection -- 8: Brand Management -- 9. Marketing Communications: Media and PR.
Keywords: Footwear industry; Fashion merchandising; Shoes -- Marketing